2014
DOI: 10.1021/es501979z
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production in Microbial Reverse-Electrodialysis Methanogenesis Cells (MRMCs) Using Thermolytic Solutions

Abstract: The utilization of bioelectrochemical systems for methane production has attracted increasing attention, but producing methane in these systems requires additional voltage to overcome large cathode overpotentials. To eliminate the need for electrical grid energy, we constructed a microbial reverse-electrodialysis methanogenesis cell (MRMC) by placing a reverse electrodialysis (RED) stack between an anode with exoelectrogenic microorganisms and a methanogenic biocathode. In the MRMC, renewable salinity gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In this sense, promising approaches to increase the microbial adhesion are (i) novel electrode materials and (ii) decrease the electrostatic repulsion of the negatively charged microbial and electrode surfaces by increasing the hydrophobicity of the electrode. Moreover, Luo et al considered using a microbial reverse-electrodialysis methanogenesis cell in order to decrease the energy requirement to overcome large cathode overpotentials [208]. In this study, the authors successfully minimized the energy by placing a reverse electrodialysis stack between the anode and the biocathode, creating a salinity gradient which was subsequently converted to electrical energy.…”
Section: Current Limitations In Electromethanogenesis and Proposedmentioning
confidence: 99%
“…In this sense, promising approaches to increase the microbial adhesion are (i) novel electrode materials and (ii) decrease the electrostatic repulsion of the negatively charged microbial and electrode surfaces by increasing the hydrophobicity of the electrode. Moreover, Luo et al considered using a microbial reverse-electrodialysis methanogenesis cell in order to decrease the energy requirement to overcome large cathode overpotentials [208]. In this study, the authors successfully minimized the energy by placing a reverse electrodialysis stack between the anode and the biocathode, creating a salinity gradient which was subsequently converted to electrical energy.…”
Section: Current Limitations In Electromethanogenesis and Proposedmentioning
confidence: 99%
“…Recently, a novel type of BES system called microbial reverse-electrodialysis electrolysis cell (MREC), which combines a reverse electrodialysis stack (RED) and MEC have been developed to drive H 2 or CH 4 generation (Kim & Logan, 2011a;Luo et al, 2014). In our previous study, the MREC system has been demonstrated as one promising system to produce high concentration of H 2 O 2 with low electrical energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel type of microbial electrochemical technologies called microbial reverseelectrodialysis cell (MRC) or microbial reverse-electrodialysis electrolysis cell (MREC), which combines a reverse electrodialysis cell (RED) with MFC or MEC have been developed to enhance electricity production and wastewater treatment or to drive H 2 or CH 4 generation [10][11][12][13][14][15]. MRC and MREC are more effective than traditional MFC and MEC on energy capture [10,12,16,17].…”
Section: Introductionmentioning
confidence: 99%